Dolní Vestonice-Pavlov : Explaining Paleolithic Settlements in Central Europe - Svoboda, Jiří, 1953- (Peopling of the Americas publication., 2020)
"Richly illustrated throughout, including beautiful color renderings of scenes from Paleolithic life suggested by Svoboda's research, this first English translation of Dolní Věstonice-Pavlov: Explaining Paleolithic Settlements in Central Europe is sure to provide not only vital information for scholars, researchers, and students but also insightful and thought-provoking background for interested general readers"--